Unusual Presentation and Surgical Treatment of a Phosphaturic Mesenchymal Tumor in a Knee - Sun, Juan; Zhou, Xi; Xia, Weibo; Wu, Huanwen; Liu, Shuzhong; Wang, Huizhen; Liu, Yong (Frontiers in Surgery, 2022)
A 30-year-old woman presented to our hospital with an 11-year history of gradually enlarging masses around the left knee and 2-year history of progressively worsening bone pain. Tumor-induced osteomalacia (TIO) was suspected, but the postoperative pathology of her two operations were both reported to be tenosynovial giant cell tumor (TGCT), which confused us, because TIO is a rare paraneoplastic syndrome caused by phosphaturic mesenchymal tumors (PMTs), not TGCT. As for the treatment, the possibility of irreformable hypophosphatemia, insufficient blood supply and innervation of the left lower limbs, as well as the unclear pathology, making performing tumor-type knee prosthesis replacement directly unreasonable. Finally, we placed articulating polymethylmethacrylate (PMMA) spacer at first, then when the blood phosphorus levels were normal, the pathology confirmed it was TIO and the blood supply and innervation was satisfying, tumor-type knee prosthesis replacement was performed. The recovery of this patient was very well, she was discharged on the 15th day after the second operation and the wound has healed well. One year after her surgery, her blood phosphorus was still in the normal range and the symptom of systemic bone pain had improved significantly.